L'impact de la distribution politico-religieuse sur le Liban. Le sport, révélateur de phénomènes sociaux?. Issue 2 (4th May 2019) - Rahal, Ziad Joseph; Campillo, Philippe; Genty, Matthieu
Abstract : Lebanon, one of the smallest countries of the Middle East, has a cultural diversity which is concentrated in its geographical space and which is difficult to see elsewhere. Its peculiarity and its originality emanate from a constitution which distributes political powers according to the religious affiliations of its population. Indeed, in Lebanon, professional sport is subjected to very strong cultural imperatives which we cannot disregard. Lebanese society, far from being secular, is colored by 19 religious groups. Sport teams belong to various politico-religious groups and the same applies to spectators. The objective of this study was born of the analysis of discussions of sports representatives and the result of a questionnaire addressed to around a hundred people, to study the impact of this politico-religious mosaic on the most popular sports discipline in Lebanon: basketball. It appears that this initially favorable management system today seems outdated and anachronistic, unsettling a social opening in a logic of globalization.